Silvopastoral systems in northern Argentine-Chilean andean Patagonia: ecosystem services provision in a complex territory. - Chillo, María Verónica (2021)
Silvopastoral systems (SPS) are sustainable production systems, characterized by a great biodiversity and multifunctionality compared with other livestock production systems. Northern Argentine-Chilean Andean Patagonia is a complex socio-ecological system where the provision and perception of ecosystem services (ES) vary depending on multiple contexts. We aim to characterize multiple ES and the associated benefits from SPS under different contexts and key factors. We propose a conceptual model of the socio-ecosystem that considers socio-historical contexts, forest ecosystems, cultural contexts, relational values, and anthropogenic aspects. We provide a deep review of published information on these factors and how these are related to the provision and perception of ES. We also consider natural and anthropogenic drivers to assist government and institutions. Finally, we discuss the main knowledge gaps that need to be addressed to attain a sustainable management. There is a need for a multidisciplinary and regional approach that can serve as a new interpretive framework for managers and decision-makers. In particular, the inclusion of relational values with nature and the visibility of anthropocentric factors can be useful tools for local development.